Genomic and immunological differences in endometrial cancer: a comparative study between young and old Asian patients - Jiang, Senwei; Li, Yunhui; Wu, Shanshan; Wan, Jing; Li, Xiaomao (Frontiers in Immunology, 2026)
BackgroundEndometrial carcinoma (EC) demonstrates a pronounced age-related disparity in clinical outcomes, yet the underlying genomic and molecular mechanisms remain incompletely characterized, especially across Asian populations.MethodsWe performed an integrated genomic analysis of two independent cohorts: the MSK-MET Asian cohort (n=94) and a Chinese EC cohort, EC-3rd-SYSU (n=18). Patients were stratified by age (young, ≤50 years; old, >50 years). We compared mutation spectra, pathway enrichment, tumor mutation burden (TMB), microsatellite instability (MSI), and survival outcomes between age groups.ResultsAcross both cohorts, PTEN, PIK3CA, and ARID1A were the most frequently mutated genes, forming a conserved oncogenic core centered on PI3K/AKT signaling and chromatin remodeling. Younger patients showed enrichment of CTNNB1 and PTEN mutations, while older patients exhibited higher frequencies of TP53, ARID1A, and MSH6 alterations. Younger tumors were characterized by activation of stemness and metabolic signaling pathways, whereas older tumors were enriched in cellular senescence, endocrine resistance, and longevity regulation pathways. No significant age-associated differences were observed in TMB or MSI status. The Chinese cohort had higher mutation rates of PTEN, KRAS, and FGFR2, while TP53 and PIK3R1 mutations were more frequent in the MSK-MET cohort. These age-specific molecular subtypes correlated with significant survival differences.ConclusionsOur study identifies conserved age-specific molecular subtypes of EC and reveals population-specific genomic features, underscoring the need for age-tailored and ethnicity-aware therapeutic strategies.